Intravital Imaging of Inflammatory Response in Liver Disease - Wang, Yang; Wang, Jing (Frontiers in Cell and Developmental Biology, 2022)
The healthy liver requires a strictly controlled crosstalk between immune and non-immune system to maintain liver function and homeostasis. A well-conditioned immune system can effectively recognize and clear noxious stimuli by self-limited, small-scale inflammatory response in physiological state. This regulated inflammatory process helps the liver coping with daily microbial exposure and metabolic stress, which is beneficial for hepatic self-renewal and tissue remodeling. However, failure of noxious stimuli clearance or dysregulation of immune response can lead to uncontrolled liver inflammation, liver dysfunction and severe liver disease. Numerous highly dynamic circulating immune cells and sessile resident immune and parenchymal cells interact and communicate with each other in an incredible complex way to regulate inflammatory response both in healthy and disease liver. Intravital imaging as a powerful tool to visualize individual cell in vivo, has been widely used for dissecting the behavior and interactions between various cell types in liver’s complex architecture. Here, we summarize some new findings provided by intravital imaging in the complexity of immune cell behavior, cell-cell interaction, and spatial organization during physiological or pathological liver inflammatory response.